למה הוא 3 * ln (x) = ln (x ^ 3)?

למה הוא 3 * ln (x) = ln (x ^ 3)?
Anonim

תשובה:

השתמש בהגדרה של logarithm ומאפיינים בסיסיים של המעריכים.

(פרטים בהמשך)

הסבר:

הגדרה בסיסית:

#color (לבן) ("XXX") ln (a) = b # אומר # e ^ b = a #

תן #s = 3 ln (x) #

#color (לבן) ("XXX") rRrr ln (x) = s / 3 #

#color (לבן) ("XXX") rRrr e ^ (s / 3) = x #

#color (לבן) ("XXX") rRrr root (3) (e ^ s) = x #

#color (לבן) ("XXX") rRrr e ^ s = x ^ 3 #

#color (לבן) ("XXX") rArrln (x ^ 3) = s #

#color (לבן) ("XXX") rArrln (x ^ 3) = 3ln (x) #